Voluntary retrenchment: voluntary or mutual separation scheme - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2015)
When an employer is facing declining business, he may be forced to make a substantial reduction in his workforce, either by way of retrenchment or through the introduction of a voluntary separation scheme ('VSS'). Unlike in the case of retrenchment, in the case of a VSS, the employer issues a circular inviting its employees to take advantage of an early retirement scheme. Under the scheme, the employer normally offers an attractive retirement package, which is better than the statutory minimum offered for retrenchment. When an employee makes an application for VSS, he is considered as offering his early retirement to the company, subject to the company's acceptance of it. When the company accepts the employee's application for VSS, the contract of employment is said to be terminated by mutual consent and it is not considered a dismissal. What is important to note in this type of scheme calling on the employees to apply for early retirement, is that by its very nature, it is done on a voluntary basis, without the employee being forced into retirement. The court cannot in equity and good conscience give effect to a purported mutual agreement which is not genuinely consensual, in particular where the employee's volitional capacity is impaired at the time he is purported to have agreed to the mutual termination. On the other hand, an agreement mutually and freely arrived at between the parties must be given effect to. In the case of the former, the onus is on the employee to establish by cogent evidence that he was forced into signing the mutual separation agreement.